2020
DOI: 10.1021/acs.jpcc.0c00087
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition and Band Alignment in 3D Covalent Organic Frameworks for Cocrystalline Organic Photovoltaics

Abstract: Covalent organic frameworks (COFs) have emerged as versatile, functional materials comprised of low-cost molecular building blocks. The permanent porosity, long-range order, and high surface area of 3D-COFs permit co-crystallization with other materials driven by supramolecular interactions. We designed a new subphthalocyanine-based 3-D covalent organic framework (NEUCOF1) capable of forming co-crystals with fullerene (C60) via periodic ball-and-socket binding motifs. The high co-crystalline surface area and l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…As is illustrated in Figure 2, the guests expected to be placed in the pores rather than populating on the surfaces of porous polymeric compounds. Similar conclusions were drawn through computational techniques [44,45]. Moreover, those studies indicated the interferences along -electrons are the main driving forces for the host-guest interactions in case of such electron-rich, conjugated host-guests [44,45].…”
Section: Techniques For Covalent Organic Framework Film Formationsupporting
confidence: 73%
See 1 more Smart Citation
“…As is illustrated in Figure 2, the guests expected to be placed in the pores rather than populating on the surfaces of porous polymeric compounds. Similar conclusions were drawn through computational techniques [44,45]. Moreover, those studies indicated the interferences along -electrons are the main driving forces for the host-guest interactions in case of such electron-rich, conjugated host-guests [44,45].…”
Section: Techniques For Covalent Organic Framework Film Formationsupporting
confidence: 73%
“…Similar conclusions were drawn through computational techniques [44,45]. Moreover, those studies indicated the interferences along -electrons are the main driving forces for the host-guest interactions in case of such electron-rich, conjugated host-guests [44,45]. The quench of photoluminescence after nitrobenzene (electron acceptor) exposure during the optical sensing applications can be a good experimental proof for this behavior [33,[46][47][48][49].…”
Section: Techniques For Covalent Organic Framework Film Formationsupporting
confidence: 69%
“…Photochemistry provides access to highly strained molecular architectures, 1 photoswitches, 2 organic photovoltaics, 3 and solar fuel materials, 4,5 which are characterized by mild conditions and high atom economy. Photochemical reactions typically consist of a series of molecular transformations that occur in excited molecules after light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Academic and industrial chemists have turned to photochemistry as a sustainable technique to construct highly strained molecular architectures 1 , photoswitches 2 , and organic photovoltaics 3 , solar fuel materials [4][5] , which are characterized by mild conditions and high atom economy. Photochemical reactions typically consist of a series of molecular transformations that occur in excited molecules after light absorption.…”
Section: Introductionmentioning
confidence: 99%